A comprehensive review on pyrazoline based heterocyclic hybrids as potent anticancer agents - Kashif Haider; Mohd Shafeeque; Shaikh Yahya; M. Shahar Yar (Elsevier, 2022)
Cancer is one of the leading causes of death globally, around 10 million deaths are reported every year due to cancer. Some clinically approved anticancer drugs play a riveting role in its treatment. Still, due to the severe emergence of drug resistance, side effects, and multidrug-resistant cancers due to mutations, it creates a significant demand for novel, potent, and safe candidates as an anticancer agent with diverse mechanisms of action. In medicinal chemistry, several heterocyclic derivatives and hybrids are studied and reported as potent anticancer agents; Pyrazoline is one of the versatile and ubiquitous scaffolds for developing novel anticancer agents. Many pyrazoline scaffolds bearing drugs are used clinically for the treatment of cancer. Few are in the late phase of the clinical trial for treating various cancers, for example, Indibulin, a novel microtubule inhibitor and AT9283. The hybridization strategy of a pyrazoline scaffold with various heterocyclic rings is very promising to minimize the side effects and drug resistance. In light of this pyrazoline containing hybrids monopolize an important place in developing potent, safe and novel anticancer agents. The presented review outlined recent advances studied and reported towards developing pyrazoline-containing hybrids as potent anticancer agents. The review covers synthetic strategy, structure-activity relationship and anticancer activities of pyrazoline hybrid derivatives. The sole purpose is to shed light on the design and development of pyrazoline hybrids compounds with high efficacy and reduced toxicity.